2022
DOI: 10.3389/fped.2022.839882
|View full text |Cite
|
Sign up to set email alerts
|

Hypertensive disorders of pregnancy and neonatal outcomes in twin vs. singleton pregnancies after assisted reproductive technology

Abstract: ObjectiveHypertensive disorders of pregnancy (HDP) are associated with an increased risk of adverse neonatal outcomes. Although twin pregnancies had a higher risk of developing HDP, it is not known whether HDP in twins will increase the risk of adverse neonatal outcomes. We aimed to assess whether this association differed in singleton and twin pregnancies in women who conceived with assisted reproductive technology (ART).MethodsWe finally included 193,590 live births born via ART from the National Vital Stati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 47 publications
0
21
1
Order By: Relevance
“…Previous studies have also con rmed an elevated risk of low Apgar scores in singleton infants affected by HDP, [27,53] although the impact on twin pregnancies may be less pronounced. [54] Importantly, our ndings revealed that HDP increased the risk of low Apgar scores, with preeclampsia having a more signi cant effect on twin infants compared to gestational hypertension. [55] The underlying pathophysiology is believed to involve placental dysfunction, which hampers fetal growth and subsequently impacts Apgar scores.…”
Section: Contrast With Other Studiesmentioning
confidence: 64%
“…Previous studies have also con rmed an elevated risk of low Apgar scores in singleton infants affected by HDP, [27,53] although the impact on twin pregnancies may be less pronounced. [54] Importantly, our ndings revealed that HDP increased the risk of low Apgar scores, with preeclampsia having a more signi cant effect on twin infants compared to gestational hypertension. [55] The underlying pathophysiology is believed to involve placental dysfunction, which hampers fetal growth and subsequently impacts Apgar scores.…”
Section: Contrast With Other Studiesmentioning
confidence: 64%
“…All articles were published between 2012 and 2022. Six of the studies ( 9 , 10 , 16 , 17 , 20 , 21 ) were from North America (USA or Canada) ( Table 1 ). The remaining were from Slovenia ( 15 ), Italy ( 11 ), the UK ( 22 ), Ireland ( 18 ), and China ( 19 ).…”
Section: Resultsmentioning
confidence: 99%
“…The remaining were from Slovenia ( 15 ), Italy ( 11 ), the UK ( 22 ), Ireland ( 18 ), and China ( 19 ). One study ( 9 ) included only assisted reproductive technology-based gestations, while all others ( 10 , 11 , 22 , 14 21 ) included natural conception as well. Seven studies ( 9 , 10 , 16 , 18 , 20 22 ) included twin pregnancies with gestational hypertension and preeclampsia.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Aspirin alone may not be able to reverse this problem. Even if ART does not increase major obstetric complications and perinatal risk in twin pregnancies [33], women who need ART may have underlying problems themselves that increase the risk of adverse pregnancy outcomes. This may also be why aspirin does not have the desired overall effect.…”
Section: Discussionmentioning
confidence: 99%